Kajian Strukturalisme Genetik Dalam Novel “Hafalan Sholat Delisa” Karya Tere Liye - Ika Zulfika (Lembaga Pengembangan Kinerja Dosen, 2024)
This research used genetic structuralisme study hat aimed to described instrinsic structure, extrinsic structure, and interpretative genitive elements of Novel “Hafalan Shalat Delisa” written by Tere Liye. This research was library research with qualitative descriptive approach. The primary data gained from the Novel of “Hafalan Shalat Delisa” and the seceondary data gained from another source that related to this research. Data collection fo this research were (1) noted and reread the novel of Hafalan Shalat Delisa written by Tere Liye, (2) analysed the whole data that related genetic structuralisme Novel “Hafalan Shalat Delisa” written by Tere Liye. The findings showed that (1) the structure of Novel Hafalan Shalat Delisa that has a theme of “ethics education” in amuslims family. The theme, plot, conflict, figure, setting and message described the good relationship, totally, and life way of delisa’s family. (2) Tere Liye as a writer of Novel “Hafalan Shalat Delisa”, really like the life founded with Islamic religious value. Her personal background was represented his Novel “Hafalan Shalat Delisa” which was full of moral and religious value, (3) Aceh community which was very religious with the majority of Moslem underwent Tsunami and Earthquake. The condition became the background of the born of the novel “Hafalan Shalat Delisa” by Tere Liye. The novel was written to memorize tsunami in Aceh in 2004. Tere Liye emphasized that the community of Aceh always consistence in holding religious teaching to the face the effect of tsunami and earthquake